Correction: Moving towards a core measures set for patient safety in perioperative care: An e-Delphi consensus study. - J P Dinis-Teixeira; Ana Beatriz Nunes; Andreia Leite; Willemijn L A Schäfer; Claudia Valli; Ismael Martínez-Nicolas; Ayshe Seyfulayeva; Pedro Casaca Carvalho; Anna Rodríguez; Daniel Arnal-Velasco; Irene Leon; Carola Orrego; et al. (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0311896.].